Using cross-wavelets to decompose the time-frequency relation between oil and the macroeconomy - Conraria, Luís Aguiar (2007)
A large body of empirical literature has suggested that oil price shocks have an important effect on economic activity. But in most of the literature the analysis is exclusively done in the time domain. However, interesting relations exist at different frequencies. We use (cross) wavelet analysis to uncover some of these relations, estimating the spectral characteristics of the time-series as a function of time. Our analysis suggests that the volatility of both the inflation rate and the output growth rate started to decrease in the decades of 1950 and 1960, suggesting that the great moderation started then,but that it was temporarily interrupted due to the oils crisis of the 1970s, whose effects extend until the mid 1980s. We also show that while at business cycle frequencies oil prices lead industrial production, in the very long run production increases lead oil price increases. The exception to this long-run relation occurred between the mid 1970s and mid 1980s. Our analysis also suggests that monetary policy became much more eficient after 1980 to deal with the inflationary pressures of oil shocks.